Rancangan Desain Data Warehouse Kunjungan Wisatawan Ke Bali Baw Tour & Travel - Sari, Ratna; Pratama, I Putu Agus Eka (Prodi Sistem Informasi FST Universitas Jambi, 2020)
This business development in the globalized era provoked fierce competition especially with the application of it to support his daily process especially in data management, therefore, the BAW Tour & Travel needs a system for data processing so that data can be stored and integrated with each other or what's called data warehouse and followed by other regulatory ETL, OLAP methods in analysis and quick decision-making. Using the data warehouse can figure out a spike in visitors' visits so it can predict people to be able to predict the number of guides during a month in case there's a spike that reduces anyone's denial of acceptance on the grounds of lack of a guide and to booked a motel because it's already full.